Opening up the black box of civil servants' competencies. Issue 1 (2nd January 2020) - Kruyen, Peter M.; Van Genugten, Marieke
ABSTRACT: Employees' competencies are key to understanding individual performance. In this article, we investigate which competencies are considered important in government using the results of a survey among civil servants. Respondents listed 248 competencies they deemed necessary for their current and future job. To some degree, these competencies can be linked to three major governance philosophies, traditional Public Administration, New Public Management, and New Public Governance, but several other meaningful clusters of competencies can be distinguished as well, including creativity-related competencies and self-development skills. Based on our results, we draw lesson for civil servants and public (human resource) managers.